Effects of the BTN162b2 mRNA COVID‐19 vaccine in humoral and cellular immunity in patients with chronic lymphocytic leukemia. Issue 1 (30th September 2022) - Fiorcari, Stefania; Atene, Claudio Giacinto; Maffei, Rossana; Mesini, Nicolò; Debbia, Giulia; Colasante, Corrado; Pozzi, Stefano; Barbieri, Emiliano; Maccaferri, Monica; Leonardi, Giovanna; Potenza, Leonardo; Luppi, Mario; et al.
Abstract: Chronic lymphocytic leukemia (CLL), the most common leukemia in the western countries, is characterized by immunosuppression due to disease itself and cytotoxic treatments. Since the beginning of COVID‐19 pandemic, patients with CLL appear to be a vulnerable population. In addition, phase III mRNA vaccine trials did not provide information about the efficacy in immunocomprised population. In CLL, the antibody‐mediated response to SARS‐CoV‐2 vaccine is impaired. The goal of this study was to evaluate the effects of SARS‐CoV‐2 vaccination on humoral immune response and on cellular immunity in CLL patients. Humoral immune response to BNT162b2 messenger RNA COVID‐19 vaccine was evaluated in 44 CLL patients comprising 20 treatment‐naïve, 14 under treatment with ibrutinib and 10 in follow‐up after completion of therapy. A positive serological response to SARS‐CoV‐2 vaccination with IgG titers higher than 13 UA/ml was detected in 54.6% of CLL patients with a higher response in patients who obtained remission after treatment. Reduced antibody response was detected in patients under ibrutinib treatment. T‐cell response to overlapping pool of peptides representing the spike region was assessed in paired CLL samples collected before and after 1 month from the second dose of COVID‐19 vaccine in treatment‐naïve and ibrutinib‐treated CLL patients using cytokine secretion assay. Both CD3+ CD4+ and CD3+ CD8+ T cells are able to mount a cellular response to spike peptides with secretion of IFNγ and TNFα before and after vaccination in both treatment naïve and ibrutinib‐treated patients and this cellular immune response is independent by COVID‐19 vaccination. Collectively, T cell response to spike peptides appeared more blunted in CLL patients under treatment with ibrutinib compared to untreated ones. Our study supports the need for optimization of vaccination strategy to achieve an adequate immune response keeping strict preventive measures by CLL patients against COVID‐19.